Roles of HLA-G/KIR2DL4 in Breast Cancer Immune Microenvironment - Zheng, Guoxu; Jia, Lintao; Yang, An-Gang (Frontiers in Immunology, 2022)
Abstract Human leukocyte antigen (HLA)-G is a nonclassical MHC Class I molecule, which was initially reported as a mediator of immune tolerance when expressed in extravillous trophoblast cells at the maternal-fetal interface. HLA-G is the only known ligand of killer cell immunoglobulin-like receptor 2DL4 (KIR2DL4), an atypical family molecule that is widely expressed on the surface of NK cells. Unlike other KIR receptors, KIR2DL4 contains both an arginine–tyrosine activation motif in its transmembrane region and an immunoreceptor tyrosine-based inhibitory motif (ITIM) in its cytoplasmic tail, suggesting that KIR2DL4 may function as an activating or inhibitory receptor. The immunosuppressive microenvironment exemplified by a rewired cytokine network and upregulated immune checkpoint proteins is a hallmark of advanced and therapy-refractory tumors. Accumulating evidence has shown that HLA-G is an immune checkpoint molecule with specific relevance in cancer immune escape, although the role of HLA-G/KIR2DL4 in antitumor immunity is still uncharacterized. Our previous study had shown that HLA-G was a pivotal mediator of breast cancer resistance to trastuzumab, and blockade of the HLA-G/KIR2DL4 interaction can resensitize breast cancer to trastuzumab treatment. In this review, we aim to summarize and discuss the role of HLA-G/KIR2DL4 in the immune microenvironment of breast cancer. A better understanding of HLA-G is beneficial to identifying novel biomarker(s) for breast cancer, which is important for precision diagnosis and prognostic assessment. In addition, it is also necessary to unravel the mechanisms underlying HLA-G/KIR2DL4 regulation of the immune microenvironment in breast cancer, hopefully providing a rationale for combined HLA-G and immune checkpoints targeting for the effective treatment of breast cancer.